نقش میانجی انعطاف پذیری روانشناختی در رابطه با عدم تحمل ابهام و استرس ادراک شده در زنان تحت درمان لقاح آزمایشگاهیThe Mediating Role of Psychological Flexibility on the Relationship Between Uncertainty Intolerance and Perceived Stress in Women Undergoing I - Pahlevani, Arezou; توکلی سحر; رحمتی دروازی سیمین (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2025)
این پژوهش به بررسی رابطه بین استرس ادراک شده و عدم تحمل ابهام (IU[1]) با نقش میانجی گری انعطاف پذیری روانشناختی در زنان تحت درمان لقاح آزمایشگاهی (IVF[2]) می پردازد. IVFیک پیشرفت پیشگامانه در پزشکی برای کمک به باروری می باشد. با این حال، چالش های هیجانی مرتبط با IVF می تواند منجر به افزایش سطح استرس در زنان شود. انعطاف‌پذیری روان‌شناختی، که به عنوان توانایی ارتباط کامل با لحظه حال و همسویی با ارزش‌های شخصی تعریف می‌شود، به‌عنوان عاملی حیاتی در ارتقای رفاه شناخته شده است. جامعه آماری پژوهش حاضر زنان تحت درمان لقاح آزمایشگاهی در بیمارستان های قم می باشد که تعداد 204 نفر از آنها به روش نمونه گیری دردسترس انتخاب شدند و به مقیاس انعطاف پذیری روانشناختی وندروال(2010)، استرس ادراک شده کوهن(1983) و عدم تحمل ابهام کارلتون(2007) پاسخ دادند. برای تجزیه و تحلیل داده ها از مدل سازی معادلات ساختاری و نرم افزار SPSS23 و ایموس استفاده شد. نتایج نشان داد که بین عدم تحمل ابهام، استرس ادراک شده و انعطاف ناپذیری روانی همبستگی مثبت وجود دارد، در حالی که انعطاف پذیری روانشناختی با عدم تحمل ابهام و استرس ادراک شده همبستگی منفی نشان داد. مدل رگرسیون ساختاری نشان داد که IU و انعطاف‌ناپذیری روان‌شناختی استرس ادراک شده را به‌طور مثبت پیش‌بینی می‌کنند، و IU با انعطاف‌پذیری روان‌شناختی ارتباط منفی دارد. این مطالعه بر اهمیت پرداختن به انعطاف‌پذیری روانشناختی در پروتکل‌های درمانی IVF برای افزایش توانایی زنان برای مقابله با استرس و عدم قطعیت‌ها تاکید می‌کند. شناخت و پرورش انعطاف‌پذیری روانشناختی می‌تواند به کاهش استرس و تحمل ابهامات زنان تحت IVF کمک کند و در نهایت نتایج درمان را بهبود بخشد. Abstract:This essay explores the relationship between perceived stress, intolerance of uncertainty (IU), and psychological flexibility in women undergoing in vitro fertilization (IVF) treatment. IVF, a groundbreaking development in reproductive medicine, offers hope to couples dealing with infertility. However, the emotional challenges associated with IVF can lead to heightened stress levels in women. The study focuses on IU and psychological flexibility as key variables influencing perceived stress.IU, characterized by a negative response to unpredictable events, is linked to various psychological disorders. Psychological flexibility, defined as the ability to be fully connected with the present moment and aligned with personal values, has been recognized as a crucial factor in promoting well-being. The study aims to explore how psychological flexibility moderates the relationship between IU and perceived stress in women undergoing IVF.A total of 204 women participated in the study, and structural equation modeling (SEM) was employed to analyze the data. The results revealed positive correlations between IU, perceived stress, and psychological inflexibility, while psychological flexibility showed a negative correlation with IU and perceived stress. The structural regression model demonstrated that IU and psychological inflexibility positively predicted perceived stress, and IU was negatively associated with psychological flexibility. Mediation analysis confirmed that psychological flexibility partially mediated the relationship between IU and perceived stress. The study emphasizes the importance of addressing emotional flexibility in IVF treatment protocols to enhance women’s ability to cope with challenges and uncertainties. Recognizing and nurturing emotional flexibility can contribute to better psychological resilience and well-being in women undergoing IVF, ultimately improving treatment outcomes. Further research is recommended to explore specific mechanisms and interventions for enhancing emotional well-being during IVF. [1] Intolerance of Uncertainty [2] In Vitro Fertilization